Sharing of Tacit Knowledge in Volunteer Portuguese Firefighters - Oliveira, Márcio (2020)
The studies in the area of knowledge management, directed to non-profit organizations are scarce, as opposed to what happens in the private and public sector. The growing importance of the third sector and its institutions, in establishing a more just and balanced society, combating asymmetries and placing itself on the side of the neediest, justifies the attention of the academic community, in order to establish and adopt best practices to carry out their missions. The choice of a case study of organizations such as the Portuguese fire brigades (FBs), unique in their action and identity, accompanies the need increasingly recognized by Portuguese society, in enabling these organizations of competencies for the best possible performance, in view of tragic events that have occurred in recent years in this country, particularly in the area of major fires. Research goal: placing the focus of the study on the sharing of tacit knowledge in these organizations and taking as a case study the Portuguese volunteer firefighter, we set as objectives the verification of the prevalence of tacit knowledge indicators within these organizations and the identification of barriers to this same sharing. Research methodology / design: a careful reading of the literature on sharing tacit knowledge allowed the identification of possible indicators and barriers to the sharing of this knowledge, which were later included in the script of interviews to eight commanders of fire brigades of the central region of Portugal, under the methodological technique snowball, for a qualitative study. Main findings: it was possible to conclude that these organizations tend not to share this type of knowledge, presenting barriers at the individual, organizational and technological level. Limitations / recommendations: as limitations of the research, it should be noted that the present research focuses exclusively on the sharing of tacit knowledge, not considering other forms of knowledge. As a case study, although with heterogeneous organizations, the same cannot be replicated to different realities.